Godsdiens: middel tot verslawing of tot heling? - W. C. Coetzer (Acta Theologica)
There are two sides to religion, on the one hand the threat that implies emotional pain and addiction, on the other hand the healing and liberating effect of a balanced and healthy religion. In this article the focus is on the former. Factors which render people vulnerable to spiritual addiction are put on the table. Similarities between a dysfunctional family system and a dysfunctional church system as well as parallels between alcoholic families and dysfunctional Christian families play a significant role in this respect. Linking up with this we have a great measure of similarity between chemical addiction and religious addiction. Further attention is given to the progressive character of the process of addiction, the process of breaking free from the sick system as well as the various areas demanding attention during the process of healing. Concerning the latter particular attention is given to behaviour which could lead to a relapse.